STRATEGI INDONESIA DALAM MEWUJUDKAN POROS MARITIM DUNIA MELALUI INDIAN OCEAN RIM ASSOCIATION (IORA) PADA TAHUN 2015-2017 - Frans Saputra Rumapea; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to review Indonesia's strategy in realizing the world maritime axis through the IORA in 2015-2017. Indonesia revives the call to become a maritime nation with the concept of the Indonesian maritime axis that is relevant to the geographical, historical and cultural potentials of the ancestors. Indonesia. Indonesia realizes the maritime axis through IORA, because IORA has six main priorities and two special areas that are relevant to the five pillars of the Indonesian maritime axis and supported by Indonesia occupying the leadership of IORA in 2015-2017.            The research applied a neorealism perspective and analyze the problem toward the research implemented a level analysis of groups with the concept of the world maritime axis. This research also implemented the theory of international cooperation. the research applied qualitative research methods and literature studies. The research collects from books, journals, documents, and the websites.            The results of this research shows that maritime culture, empowering marine resources, maritime connectivity, maritime diplomacy and maritime defences are way the essential to world maritime axis. In efforts to optimize the maritime axis, Indonesia cooperates with South Africa, Sri Lanka and Mozambique. Indonesia by IORA expand and dominate African countries. Keywords: Strategy, Maritime Axis, IORA.